Experimental seismic investigation of Sefid rud concrete buttress dam model on shaking table. - Ghaemmaghami, A.R (Earthquake engineering & structural dynamics.)
Owing to the devastating M7.6 earthquake of 20 June 1990 that occured in the northern province of Iran, Sefid-rud concrete buttress dam located near the epicenter was severely shaken. The crack penetrated throughout the dam thickness near slope discontinuity, causing severe leakage, but with no general failure. In this study, nonlinear seismic response of the highest monolith with empty reservoir is investigated experimentally through model testing. A geometric scaled model of 1:30 was tested on a shaking table with high frequency capability to study dynamic cracking of the model and serve as data for nonlinear computer model calibration. Three construction joints are set up in the model to simulate effects of construction aspects. The experimental results are then compared with smeared crack and damage mechanics finite element simulations using nonlinear concrete constitutive models based on fracture mechanics. The crack patterns obtained from numerical models are in good agreement with those obtained from shaking table tests for the case of including construction joint effects and rigid foundation.